Fucoidan inhibits apoptosis and improves cardiac remodeling by inhibiting p53 transcriptional activation through USP22/Sirt 1 - Wang, Shuai; Bai, Jie; Che, Yilin; Qu, Weikun; Li, Jing (Frontiers in Pharmacology, 2023)
Background: Humans with hypertensive heart disease are more likely to experience heart failure, arrhythmia, myocardial infarction, and sudden death, and it is crucial to treat this condition. Fucoidan (FO) is a natural substance derived from marine algae that has antioxidant and immunomodulatory activities. FO has also been shown to regulate apoptosis. However, whether FO can protect against cardiac hypertrophy is unknown. Methods: We investigated the effect of FO in hypertrophic models in vivo and in vitro. C57BL/6 mice were given an oral gavage of FO (300 mg/kg/day) or PBS (internal control) the day before surgery, followed by a 14-day infusion of Ang II or saline. AC-16 cells were treated with si-USP22 for 4 h and then treated with Ang II (100 nM) for 24 h. Systolic blood pressure (SBP) was recorded, echocardiography was used to assess cardiac function, and pathological changes in heart tissues were assessed by histological staining. Apoptosis levels were detected by TUNEL assays. The mRNA level of genes was assessed by qPCR. Protein expression was detected by immunoblotting. Results: Our data showed that USP22 expression was lowered in Ang II-infused animals and cells, which could promote cardiac dysfunction and remodeling. However, treatment with FO significantly upregulated the expression of USP22 and reduced the incidence of cardiac hypertrophy, fibrosis, inflammation, and oxidative responses. Additionally, FO treatment lowered p53 expression and apoptosis while increasing Sirt 1 and Bcl-2 expression. Conclusion: By reducing the level of Ang II-induced apoptosis through the regulation of USP22/Sirt 1 expression, FO treatment might improve cardiac function. According to this study, FO might be potential targeted approach for treating heart failure.